The Impact of the Force Intervention Brigade’s Use of Offensive Force in Attaining Peace in the Democratic Republic of the Congo: Lessons Learnt - Ibuge, Wilbert Augustin; Nguyahambi, Ajali Mustafa; Sansa, Godfrey Emiliano (Technium Social Sciences Journal, 2026)
The Force Intervention Brigade (FIB) was established in 2013 as the most uniquely armed brigade in the history UN peace operations to promote security in the Democratic Republic of the Congo (DRC). Among others, the Force was mandated first, to use all necessary means to protect civilians, humanitarian personnel and human rights defenders and to support the Government of the DRC in stabilization and peace consolidation efforts. Second, to adhere to the core principles of peacekeeping operations – consent of the parties to the conflict, impartiality, and non-use of force. While the FIB registered tactical successes within a short time after its deployment, a myriad of challenges beset it subsequently, essentially generating serious questions on the impact FIB’s use of offensive force has had in contributing to the quest for the attainment of peace and promotion of security in the DRC. The main argument is that the FIB’s offensive use of force, while demonstrably suitable in the shorter term in addressing the threat posed by the Movement of March 23 (M23) rebel group against civilians and stability in eastern DRC, questions still remain on how such use of force can sustainably be balanced with the requirement for the UN force to adhere to the core principles of UN peacekeeping (i.e. consent of the parties to the conflict, impartiality, and non-use of force). As such, this article examines the conflicting realities, at the tactical or micro-level, between the execution of robust mandates and the maintenance of basic norms of peacekeeping norms. The findings show that, while offensive force can deter the violence and impunity meted by armed groups (AGs) in the shorter term, it rarely has the ability to secure lasting peace, partly due to the enduring political, social, and structural set up obtaining in the conflict area and beyond. The study concludes that, to achieve durable peace, military action of any magnitude must be firmly in support of the political process and dialogue, local community engagement, and post-conflict development.